Stock pledge, risk of losing control and corporate innovation - Pang, Caiji; Wang, Ying (Journal of Corporate Finance, 2020)
This paper investigates the effects of stock pledge by controlling shareholder on corporate's future innovation productivity and the mechanism through which stock pledge affects innovation. We find that both the existence of stock pledge by controlling shareholder and the percentage of shares pledged by controlling shareholder are significantly negatively related to firms' future innovation outputs and quality, and these baseline results are robust to a variety of tests on sample selections, model specifications, and variable definitions. We further adopt several methodologies to address endogeneity concerns and establish a causal relationship between stock pledge by controlling shareholder and innovation. We then provide evidence to show that the impediment effect of stock pledge by controlling shareholder on innovation is possibly due to controlling shareholder's fear of losing corporate control in case of innovation failure. Finally, we find that although stock pledge is a possible channel to relieve a firm's financial constraint, it does not encourage the firm to invest more in innovation.